KEGIATAN EKSTRAKURIKULER MUHADHARAH SEBAGAI SARANA PEMBENTUKAN SELF CONFIDENCE SANTRI DI MA’HAD TARBIYATUL MUSTAFID NARMADA - Ahmad Faisal; Erlan Muliadi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the implementation of extracurricular muhadharah activities as a means of building self-confidence in students, as well as supporting and inhibiting factors at Ma'had Tarbiyatul Mustafid Narmada. This study uses a qualitative approach with a case study type. Data collection techniques were carried out through observation, interviews, and documentation. The research data sources consisted of the leadership of the ma'had, the supervising ustadz, and students. Data analysis used the Miles and Huberman model through the stages of data reduction, data presentation, and drawing conclusions. The results showed that muhadharah activities were carried out routinely every Friday night by involving students in various roles such as MC, Al-Qur'an reading, speeches, and prayers. This activity was able to increase the courage, speaking skills, and self-confidence of students in appearing in public. Supporting factors for this activity include motivation from the ustadz and parental support, while inhibiting factors include the lack of facilities and the low interest of some students in participating in muhadharah activities. Thus, muhadharah activities have an important role as a means of building self-confidence in students in the Islamic boarding school environment.